Dementia and Mild Cognitive Impairment: An Overview - Wada, Kenji (Nō shinkei geka, 2025)
Dementia and mild cognitive impairment (MCI) are common and increasingly encountered clinical syndromes in neurology and neurosurgery, especially in an aging society. With Japan undergoing a rapid demographic shift, addressing cognitive decline in older adults has become an urgent public health concern. This review provides an overview of dementia and MCI, focusing on the epidemiology, definition, etiology, disease progression, diagnosis, treatment, and post-diagnostic support. Through this discussion, we aim to offer practical insights for neurosurgeons and other specialists caring for patients with cognitive impairment.